The Cloister and the Crime: Medieval Monks in Modern Murder-Mysteries. (4th January 2016) - Foot, Sarah
Abstract : The monastic day continued at its steady, unhurried, unvarying pace. Vespers was sung in church, followed by a light supper of bread and fruit, washed down with a glass of ale. Kenelm and Elaf were absent from the table, however. Hungry by the time of Vespers, they were famished when the bell for Compline summoned the monks to the last service of the day. As they shuffled off to the dormitory with the other novices, they were feeling the pangs with great intensity. Escaping the dormitory to look for something to eat as soon as their peers were asleep, the novices are disturbed and take refuge in the bell tower. There Elaf falls across an obstruction and lets out a yell of sheer terror: he is lying across the stiff, stinking body of a man. 'The missing Brother Nicholas had at last been found'.